2023
DOI: 10.3390/jcm12155051
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Health-Related Quality of Life, Anxiety and Depression in Patients with Inclusion Body Myositis: A Register-Based Cross-Sectional Study in Germany

Abstract: Inclusion body myositis (IBM) is a rare neuromuscular disease and the most prevalent idiopathic inflammatory myopathy (IIM) in patients aged older than 50 years. A systematic review has shown that no clear-cut conclusions can be drawn about the health-related quality of life (HRQoL) and mental health in IBM. We aimed to assess the HRQoL and mental health, to explore associated disease-related and socioeconomic factors as well as the utilization of psychological support in German IBM patients. This cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(70 reference statements)
0
3
1
Order By: Relevance
“…The results of this study revealed symptoms of moderate to severe depression in 78.2% of participants. This finding contrasts with a study by Senn et al, who found only 37.8% of their participants had symptoms of depression at all 28 . The study assessed participants with IBM in Germany via the Hospital Anxiety and Depression Scale German version, therefore a direct comparison is not possible.…”
Section: Discussioncontrasting
confidence: 96%
“…The results of this study revealed symptoms of moderate to severe depression in 78.2% of participants. This finding contrasts with a study by Senn et al, who found only 37.8% of their participants had symptoms of depression at all 28 . The study assessed participants with IBM in Germany via the Hospital Anxiety and Depression Scale German version, therefore a direct comparison is not possible.…”
Section: Discussioncontrasting
confidence: 96%
“…Lanis 1 , H. Alexanderson 2 , K. Ardalan 3 , S. Edison 4 , C.D. Graham 5 , I. de Groot 6 , L. Gupta 7,8 , S. Kim 9 , A.M. Knight 10,11 , L. Kobert 12 , P. Livermore 13 , C. Lood 14 , C. Pilkington 13 , M. Regardt 15,16 , T.B. Rubinstein 17,18 , S. Shenoi 1 , L. Turnier 19 , N.B.M.…”
Section: Mental Health In Paediatric and Adult Myositis-related Disea...mentioning
confidence: 99%
“…Another study observed that one-fifth of those with inclusion body myositis (IBM) presented with significant levels of anxiety or depression (11). Adults with IIMs in 48 countries similarly conveyed high cognitive impact, difficulty sleeping, and emotional distress (12).…”
Section: Mental Health In Paediatric and Adult Myositis-related Disea...mentioning
confidence: 99%
“…Myositis mainly affects proximal muscles in arms and legs as well as neck flexors leading to physiological, physical and psychological impairment negatively affecting quality of life and health. [1][2][3][4] Other organs are frequently involved such as joints, skin, lung, gastrointestinal tract and the heart, further negatively affecting outcome for patients with IIM. Treatment is based on high doses of glucocorticoids in combination with immunosuppressive drugs over a long period of time, often lasting for several years, and with disappointing results with persisting irreversible chronic manifestations such as muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%